Flouting of Conversational Maxims Analysis of Characters and Social Contexts in “All The Bright Places” Movie - Aulia Zahra Tasyarasita; Agus Hari Wibowo (Faculty of Language and Literature, University of Surakarta, 2022)
This research is carried out to investigate the types of flouting of maxims and the strategies used by the characters that occur within the background of power and social distance contexts in